Differential influence of elevated CO2 on gas exchange and water use efficiency of four indigenous shrub species distributed in different sandy environments in central Inner Mongolia - Li, Qiaoyan; Lai, Liming; Zhou, Jihua; Du, Hui; Guan, Tianyu; Zhang, Xiaolong; Jiang, Lianhe; Zheng, Yuanrun; Yu, Yi; Gao, Yong; An, Ping; Shimizu, Hideyuki (Ecological Research, 2018)
In view of the increase in global warming and carbon dioxide (CO 2 ) concentrations, it is essential to investigate the influences of climate change on plant growth and water use in arid and semi-arid grassland species. Experiments were conducted to understand the ecophysiological response of four indigenous species to elevated CO 2 in the semi-arid sandy grassland of central Inner Mongolia. Seedlings of the four species were grown for 8 weeks at four different consistently elevated CO 2 concentrations in the environment-controlled growth chambers. All four elevated CO 2 concentrations (400, 800, 1200, 1600 ppm) were found to result in decreased stomatal conductance (26–86%), decreased transpiration rate (21–80%), increased shoot water potential (1–42%) and increased water use efficiency (WUE) (10–412%) for two Artemisia species and Caragana korshinskii . Under our experimental conditions, the two Artemisia species and C. korshinskii would benefit more than Hedysarum laeve from exposure to elevated CO 2 in terms of higher shoot water potential and WUE combined with lower stomatal conductance and transpiration rate. The results indicate that in a warmer, CO 2 -enriched future atmospheric environment, WUE in semi-arid grasslands may be higher than previously expected. Our findings will provide information for screening appropriate species for restoration of the degraded sandy grasslands in semi-arid areas under future climate change scenarios.